Análisis del procedimiento de contratación con proveedores internacionales en la ley orgánica del sistema nacional de contratación pública y su reglamento - Barreno Moncada, Salomé (2014)
Procurement represents an essential activity between State and suppliers, thus allows Management to obtain goods and services from the society in Exchange to an economic reward, improving the development of activities of people in a specific territory. In some cases, it is far more convenient that the State obtain those goods and services in an international level, but there is no regulation in topics such as international procurement which becomes a limiting for the fulfillment of the Public Institutions activities. In Ecuador, there is a regular need to conduct negotiations with foreign suppliers, with the obvious benefits for the State. However, there is no normative to regulate that kind of contracts, it is necessary to establish a proposal to develop some uniform criteria for the acquisition of goods and services of the Public Institutions in the country. As it is stated by the procurement principles, it is convenient to find the better offers in the markets, with benefits for the country, and that is why the procurement with foreign suppliers must be considered, to achieve better benefits related with governmental activities. In the same way, it is important to establish suggestions to avoid problems in these kinds of contracts, fixing guidelines of the authorities and control entities in the time of the signature of the above mentioned contracts. The need to have those procedures regulations based on the actual Laws in procurement will let the contractor entities to know how to manage contracts with suppliers under the same modality and thus, while there is no normative related to foreign matters and the need to have international procedures, it is important for Public Management the reform of the Organic Law of the National Procurement System as well as its General Regulation to include the international processes with the correspondent parameters, as they are in force for the other procurement procedures.